MOTYW LIPY CZARNOLESKIEJ W PISMACH CYPRIANA NORWIDA – W KONTEKŚCIE NORWIDOWSKIEGO MYŚLENIA O SZTUCE - Łuczak, Bartłomiej (Colloquia Litteraria, 2017)
The article offers an interpretation of the linden of Czarnolas motif present in Norwid’s poem Do Nikodema Biernackiego from 1857 and his letter to Józef Bohdan Wagner from 1874. The author touches upon Norwid’s artistic identity in the context of the poet’s rooting in the Renaissance culture. Furthermore, Łuczak attempts to cast some light on the Norwidian category of originality, which was tightly related to his thinking about art. The article points to how Norwid perceived various ways in which artists processed folk culture. Finally, the article underscores the concurrence of references to aesthetic issues which the nineteenth-century poet makes in multiple texts.